Unusual central indian drought of summer monsoon 2008: role of southern tropical indian ocean warming - Rao, Suryachandra A.; Chaudhari, Hemantkumar S.; Pokhrel, Samir; Goswami, B. N. (Journal of Climate, 2010)
While many of the previous positive Indian Ocean dipole (IOD) years were associated with above (below)normal monsoon rainfall over central (southern) India during summer monsoon months [June-September (JJAS)], the IOD event in 2008 is associated with below (above)-normal rainfall in many parts of central (southern peninsular) India. Because understanding such regional organization is a key for success in regional prediction, using different datasets and atmospheric model simulations, the reasons for this abnormal behavior of the monsoon in 2008 are explored. Compared to normal positive IOD events, sea surface temperature (SST) and rainfall in the southern tropical Indian Ocean (STIO) in JJAS 2008 were abnormally high. Downwelling Rossby waves and oceanic heat advection played an important role in warming SST abnormally in the STIO. It was also found that the combined influence of a linear warming trend in the tropical Indian Ocean and warming associated with the IOD have resulted in abnormal warming of the STIO. This abnormal SST warming resulted in enhancement of convection in the southwest tropical Indian Ocean and forced anticyclonic circulation anomalies over the Bay of Bengal and central India, leading to suppressed rainfall over this region in JJAS 2008. The above mechanism is tested by conducting several model sensitivity experiments with an atmospheric general circulation model (AGCM). These experiments confirmed that the subsidence over central India and the Bay of Bengal was forced mainly by the anomalous warming in the STIO region driven by coupled ocean-atmosphere processes. This study provides the first evidence of combined Indian Ocean warming, associated with global warming, and IOD-related warming influence on Indian summer monsoon rainfall. The combined influence may force below-normal rainfall over central India by inducing strong convection in the STIO region. The conventional seesaw in convection between the Indian subcontinent and the eastern equatorial Indian Ocean may shift to the central equatorial Indian Ocean and the Bay of Bengal if the central Indian Ocean consistently warms in the global warming scenario.

Long-lived monsoon depressions of 2006 and their linkage with the Indian ocean Dipole - Krishnan, R.; Ayantika, D. C.; Kumar, Vinay; Pokhrel, Samir (International Journal of Climatology, 2011)
A highlight of the 2006 boreal summer monsoon season was the enhanced activity of long-lived monsoon depressions and low-pressure systems (LPS) over the Indian region. Another important phenomenon during this period was the evolution of a positive Indian Ocean Dipole (PIOD) event. Although previous studies have investigated the impact of PIOD on the large-scale monsoon response, their influence on monsoon LPS activity is not well understood. Based on detailed diagnostic analyses of monsoon LPS during 2006, as well as those associated with other PIOD events during 1958-2007, the present work addresses two specific issues concerning the roles of (a) PIOD-induced large-scale circulation changes and (b) internal feedbacks between latent heating and dynamics, in sustaining the monsoon LPS activity. The results show that PIOD conditions generally favour increased propensity of long-lived (>5 days) LPS with long westward tracks extending into northwest India. The average contribution of long-lived monsoon LPS to the total is found to be approximately 12% higher during PIOD episodes as compared to non-PIOD. The PIOD events showed two important large-scale elements conducive for enhancement of LPS activity: (a) strengthening of cross-equatorial moisture transport from south-eastern tropical Indian Ocean into the Bay of Bengal and (b) enrichment of barotropic instability of monsoon flow. Estimates of latent-heating profiles from TRMM-satellite products during the 2006 LPS showed heating in the mesoscale updrafts above 600 hPa with maximum approximately 400 hPa; while cooling prevailed in lower levels. Stratiform precipitation covered approximately 70-85% of rain area during the prolonged LPS; and the large-scale monsoon Hadley-type circulation was found to be intensified with strong mid-level inflows entering the stratiform rain region. The overall findings suggest that the PIOD-induced background circulation together with internal feedbacks between mesoscale convective systems and large-scale circulation can effectively enhance the longevity of monsoon LPS. These results should serve as important inputs for numerical weather forecasting of extreme rainfall events associated with the regional monsoon phenomenon. Copyright (C) 2010 Royal Meteorological Society
Keywords: Indian ocean dipole; life period; monsoon depressions

Seasonal prediction of Indian summer monsoon in NCEP coupled and uncoupled model - Chaudhari, Hemantkumar S.; Pokhrel, Samir; Mohanty, Sachiko; Saha, Subodh K. (Theoretical and Applied Climatology, 2013)
This study has identified probable factors that govern ISMR predictability. Furthermore, extensive analysis has been performed to evaluate factors leading to the predictability aspect of Indian Summer Monsoon Rainfall (ISMR) using uncoupled and coupled version of National Centers for Environmental Prediction Coupled Forecast System (CFS). It has been found that the coupled version (CFS) has outperformed the uncoupled version [Global Forecast System (GFS)] of the model in terms of prediction of rainfall over Indian land points. Even the spatial distribution of rainfall is much better represented in the CFS as compared to that of GFS. Even though these model skills are inadequate for the reliable forecasting of monsoon, it imparts the capacious knowledge about the model fidelity. The mean monsoon features and its evolution in terms of rainfall and large-scale circulation along with the zonal and meridional shear of winds, which govern the strength of the monsoon, are relatively closer to the observation in the CFS as compared to the GFS. Furthermore, sea surface temperature-rainfall relation is fairly realistic and intense in the coupled version of the model (CFS). It is found that the CFS is able to capture El Nio Southern Oscillation ISMR (ENSO-ISMR) teleconnections much strongly as compared to GFS; however, in the case of Indian Ocean Dipole ISMR teleconnections, GFS has the larger say. Coupled models have to be fine-tuned for the prediction of the transition of El Nio as well as the strength of the mature phase has to be improved. Thus, to sum up, CFS tends to have better predictive skill on account of following three factors: (a) better ability to replicate mean features, (b) comparatively better representation of air-sea interactions, and (c) much better portrayal of ENSO-ISMR teleconnections. This study clearly brings out that coupled model is the only way forward for improving the ISMR prediction skill. However, coupled model's spurious representation of SST variability and mean model bias are detrimental in seasonal prediction.